Advance Directives and Alzheimer's Disease. Issue 3 (September 2018) - Davis, Deena S.
Americans who are afraid of living for many years with Alzheimer's might seek a way to end their lives early, when their dementia has just entered the moderate phase. There is no legal process for doing so. In this paper I argue that advance directives, in particular, are not a legal solution for those who prefer to die rather than suffer years of dementia. The problem is that an advance directive only works to hasten death when there is a life-threatening illness for which one can refuse treatment; more often than not, Alzheimer's kills the self long before it kills the body.